2014
DOI: 10.1007/s00894-014-2140-9
|View full text |Cite
|
Sign up to set email alerts
|

Water-mediated potassium acetate intercalation in kaolinite as revealed by molecular simulation

Abstract: Molecular simulations are suitable tools to study the adsorption and intercalation of molecules in clays. In this work, a recently proposed thermodynamically consistent force field for inorganic compounds (INTERFACE, Heinz H, Lin TJ, Mishra RK, Emami FS (2013) Langmuir 29:1754-1765), which enables accurate simulations of inorganic-organic interfaces, was tested for a two-sheet type clay mineral. All-atom NpT molecular dynamics simulations were used to describe the characteristics (basal spacing, loading, molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…The pressure coupling is semi-isotropic in that only pressures in x-and y-directions are isotropic while different in z-direction. 35 …”
Section: Simulation Settingsmentioning
confidence: 97%
“…The pressure coupling is semi-isotropic in that only pressures in x-and y-directions are isotropic while different in z-direction. 35 …”
Section: Simulation Settingsmentioning
confidence: 97%
“…To address such issues, molecular dynamics (MD) simulations have become an effective way for the study of interfacial systems by providing the atomic level information in many aspects complementary to the experimental data. To our best knowledge, only a few MD simulation studies have been reported on high polar organics intercalated into the galleries of kaolinite [23][24][25][26][27][28]. However, the kaolinite intercalation complexes in these researches were constructed according to the ideal model system.…”
Section: Introductionmentioning
confidence: 97%
“…For all the amides, we detected a second stable state (type-2) at higher guest molecule contents, but the identification of this state is subject to higher uncertainty. Although the reality of these complexes is still an open question, it is indirectly confirmed by the experimentally proven existence of a second kaolinite intercalation complex with potassium (and also ammonium) acetate [23,25,27].…”
Section: Identification Of Stable Complexesmentioning
confidence: 98%
“…Adsorption and intercalation of molecules in clays are effectively studied by means of such techniques [19][20][21][22][23][24], uncovering material features that are currently not available from experiments. In our earlier studies we provided predictions by molecular simulations for intercalation complexes with potassium and ammonium acetates [25][26][27], methanol [28], and cetyltrimethylammonium chloride [29], using the standard allatom force field, CHARMM [30], and its highly realistic extension for kaolinite, INTERFACE [31].…”
Section: Introductionmentioning
confidence: 99%